Acute Schistosoma mansoni infection increases susceptibility to systemic SHIV clade C infection in rhesus macaques after mucosal virus exposure. - Agnès-Laurence Chenine; Ela Shai-Kobiler; Lisa N Steele; Helena Ong; Peter Augostini; Ruijiang Song; Sandra J Lee; Patrick Autissier; Ruth M Ruprecht; W Evan Secor (Public Library of Science (PLoS), 2008)
Individuals living in sub-Saharan Africa represent 10% of the world's population but almost 2/3 of all HIV-1/AIDS cases. The disproportionate HIV-1 infection rates in this region may be linked to helminthic parasite infections that affect many individuals in the developing world. However, the hypothesis that parasite infection increases an individual's susceptibility to HIV-1 has never been prospectively tested in a relevant in vivo model.We measured whether pre-existing infection of rhesus monkeys with a parasitic worm would facilitate systemic infection after mucosal AIDS virus exposure. Two groups of animals, one consisting of normal monkeys and the other harboring Schistosoma mansoni, were challenged intrarectally with decreasing doses of R5-tropic clade C simian-human immunodeficiency virus (SHIV-C). Systemic infection occurred in parasitized monkeys at viral doses that remained sub-infectious in normal hosts. In fact, the 50% animal infectious (AID(50)) SHIV-C dose was 17-fold lower in parasitized animals compared to controls (P<0.001). Coinfected animals also had significantly higher peak viral RNA loads than controls (P<0.001), as well as increased viral replication in CD4(+) central memory cells (P = 0.03).Our data provide the first direct evidence that acute schistosomiasis significantly increases the risk of de novo AIDS virus acquisition, and the magnitude of the effect suggests that control of helminth infections may be a useful public health intervention to help decrease the spread of HIV-1.